Restriction Endonuclease Mapping of the Proviral DNA of the Exogenous RIII Murine Mammary Tumor Virus - Etkind, Polly R. (1982)
Cellular DNA containing integrated murine mammary tumor virus (MuMTV) was isolated from FeI/C6 feline kidney cells and CCL64 mink lung cells infected with milkborne RIII MuMTV. By using restriction enzyme HpaI, intact RIII MuMTV provirus (length, 8.7 kilobases [kb]) was excised from the cellular DNA. Subsequent restriction endonuclease analysis of this HpaI fragment with KpnI, HindIII, EcoRI, BamHI, BglII, PstI, SstI, SalI, and XhoI enabled us to construct a map of the RIII virus genome. A comparison of this map with the maps of the GR and C3H MuMTV's revealed that there are greater sequence differences between the RIII virus and the GR and C3H MuMTV proviruses than there are between the GR and C3H proviruses. The following are features of the restriction map unique to the RIII provirus: the presence of three BamHI and two EcoRI cleavage sites, a HpaI cleavage site in the terminal 3′-5′ repeat unit of the provirus, and the absence of an XhoI cleavage site. Another distinguishing feature of the RIII provirus is that the sizes of some of the restriction fragments produced by cleavage of the RIII provirus with PstI are different from the sizes of the fragments obtained by PstI cleavage of the GR and C3H proviruses. Like the GR proviral DNA, the RIII proviral DNA has three SstI (SacI) cleavage sites, whereas the C3H provirus has only two SstI sites. HpaI digestion of MuMTV-infected mink lung cell DNA revealed only one class of provirus (an 8.7-kb fragment); however, we observed several minor classes of RIII proviral DNA in addition to the major class of provirus DNA in infected cat kidney cells. PstI digestion of the HpaI 8.7-kb fragments from both feline and mink cells generated a 3.7-kb DNA fragment identical in size to a PstI-generated fragment that has been found in GR and C3H milkborne virus-infected cells. Although a fragment similar in size to the milkborne 3.7-kb PstI fragment has been found as an endogenous component in many C3H and GR mouse tissues, we did not observe such an endogenous fragment in the RIII mouse strain. Therefore, the 3.7-kb fragment may be useful as a marker for the milkborne RIII MuMTV provirus in RIII mice.